The origin of prostate gland-secreted IgA and IgG. Issue 1 (December 2017) - Silva, Juliete; Biancardi, Manoel; Stach-Machado, Dagmar; Reis, Leonardo; Sant'Anna, Osvaldo; Carvalho, Hernandes
Abstract The prostate secretes immunoglobulin (Ig) A (IgA) and IgG; however, how immunoglobulins reach the secretion, where the plasma cells are located, whether immunoglobulins are antigen-specific and where activation of the adaptive response occurs are still unknown. Immune cells, including CD45RA+ cells, were scattered in the stroma and not organized mucosae-associated lymphoid-tissue. IgA (but not IgG) immunostaining identified stromal plasma cells and epithelial cells in non-immunized rats. Injected tetramethylrhodamine-IgA transcytosed the epithelium along with polymeric immunoglobulin receptor. Oral immunization with ovalbumin/mesopourous SBA-15 silica adjuvant resulted in more stromal CD45RA+ /IgA+ cells, increased content of ovalbumin-specific IgA and IgG, and the appearance of intraepithelial CD45RA+ /IgG+ cells. An increased number of dendritic cells that cooperate in other sites with transient immunocompetent lymphocytes, and the higher levels of interleukin-1β, interferon-γ and transforming growth factor-β, explain the levels of specific antibodies. Nasal immunization produced similar results except for the increase in dendritic cells. This immunomodulatory strategy seems useful to boost immunity against genitourinary infections and, perhaps, cancer.